Earnings thresholds among the listed Brazilian enterprises: A strategy to avoid earnings loss or earnings decreased - Liu, Zhenjia (Review of Business Management, 2023)
Purpose – Few studies have analyzed how enterprise managers manipulate business activities to meet the earnings thresholds of Brazilian listed companies. This study investigates whether Brazilian listed companies manipulate their business activities to meet their earnings thresholds. Theoretical framework – This study verifies whether Brazilian listed companies manipulate their business activities to meet their earnings thresholds and whether this behavior is consistent with the signaling theory. Design/methodology/approach – We employ the Deng model (2018) and analyze how firms manipulate their earnings using gains or losses from property disposition and whether they attempt to meet their earnings thresholds by avoiding earnings losses and decreases. A regression model is then used to verify whether the manipulation affects performance in the following period (i.e., sends signals). A total of 314 samples from 49 Brazilian listed companies during 2011-2018 are examined. Findings – Most Brazilian listed companies do not manipulate their gains or losses from property disposition to avoid earnings losses or decreases, and the manipulation does not affect performance in the following period. Therefore, the signals do not reflect future expectations, thus rejecting the signaling theory. Practical & social implications of research – Enterprise managers could carefully control operating activities. Creditors could monitor business transactions. Accountants should pay attention to monitoring their real earnings, seeking to align the exercise of manager judgment with practices that improve the quality of accounting information. The board of directors could strengthen its control over the property disposition behavior of enterprise managers. Originality/value – This study is the first to verify the earnings manipulation behavior of Brazilian firms by using the signaling theory. We also analyze the manipulation of the gains or losses from property disposition to address the gap in the literature. Keywords: Earnings thresholds, Brazil, avoiding earnings below zero, avoiding earnings decreases, manipulating property disposition.